La domestique comme figure de l’intersectionnalité dans le cinéma argentin : L’Enfant-poisson (Lucía Puenzo, 2009) - Laurence Mullaly (Mise au Point)
The objective of this work is to propose a study associating transfeminist theorization and filmic analysis of an Argentine film, The Fish Child, by Lucía Puenzo (2009) which portrays the figure of the domestic servant in an interracial and lesbian melodrama. My hypothesis is that the "mucama", which is difficult to translate into French because it refers to a singular socio-historical reality, is the object of increasing attention in Latin American cinema, as well as in the field of social sciences, from a developing decolonial transfeminist perspective. The study of the film will attempt to highlight the representation of intersectionality, that is, the contextualized consideration of the intertwined nature of different forms of discrimination (race, class, gender) in Lucía Puenzo's representation, through her character of the mucama.